2019
DOI: 10.3390/buildings9100210
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Scientometric Analysis of Global Building Information Modeling (BIM) Research in the Architecture, Engineering and Construction (AEC) Industry

Abstract: : In the recent decade, Building Information Modeling (BIM) has widely been adopted in the Architectural, Engineering and Construction (AEC) industry and completely upended the way we build. While BIM continues gain momentum in the industry, it has also attracted increasing attention from researchers. However, most of the current study focuses on reviewing BIM for management, BIM for green building, BIM for infrastructure and BIM for Facilities Management (FM). There are few studies about Global BIM review and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 57 publications
0
40
0
2
Order By: Relevance
“…Considering the evolution imposed by the use of BIM, Table 1 summarizes the basic differences between the possibilities of using the BIM model in the construction process and the possibilities of CAD software supporting the traditional construction process. Based on their research of publications on BIM published since 2004, Liu et al [9] concluded that, in the recent decade, the research in the field of BIM was developing continuously, which had completely subverted the traditional operation mode of the AEC industry and attracted more and more researchers' attention at the same time. Considering the advantages of BIM technology and the pace of its development in many countries around the world, but also taking into account the disadvantages of this technology, the authors decided to investigate the trends in its development in Poland.…”
Section: Bim Technologymentioning
confidence: 99%
“…Considering the evolution imposed by the use of BIM, Table 1 summarizes the basic differences between the possibilities of using the BIM model in the construction process and the possibilities of CAD software supporting the traditional construction process. Based on their research of publications on BIM published since 2004, Liu et al [9] concluded that, in the recent decade, the research in the field of BIM was developing continuously, which had completely subverted the traditional operation mode of the AEC industry and attracted more and more researchers' attention at the same time. Considering the advantages of BIM technology and the pace of its development in many countries around the world, but also taking into account the disadvantages of this technology, the authors decided to investigate the trends in its development in Poland.…”
Section: Bim Technologymentioning
confidence: 99%
“…This study proved that clash detection could reduce construction waste from 4.3% to 15.2%. Jalaei et al developed an add-on to the BIM that quantifies the amount of waste prevented by different BIM potentials and the resulting environmental impacts [8] in that the proposed framework showed that BIM could reduce the energy consumed and CO 2 emitted by about 66.1 MJ and 62.2%, respectively. However, the abovementioned strategies have not been adopted in practice as widely as was anticipated.…”
Section: Bim In Cwmmentioning
confidence: 99%
“…The BIM can be employed to improve the quality, accuracy, and efficiency of construction processes by optimizing the design, choosing the appropriate materials, increasing collaboration between stakeholders, providing well services, and facilitating chronological deconstruction, ultimately reducing the RWG [8]. Each of these enhancements to current construction activities can act as a chain of prerequisites for the others to occur.…”
Section: Model and Variable Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…De acuerdo con Salinas y Prado (2019), los referentes a nivel mundial en el desarrollo de estándares y normativas BIM son Estados Unidos, Reino Unido y Singapur. Para Liu, Lu y Chang Peh (2019), EE.UU. es el país con más investigaciones en el campo del BIM.…”
unclassified